Registration of 01Ab9663 Spring Malting Barley Germplasm. Issue 3 (25th May 2017) - Hu, G.; Obert, D. E.; Evans, C. P.; Satterfield, K.; Ellberg, S.; Marshall, J. M.; Martin, C.
Abstract : Enlarging genetic pools of barley ( Hordeum vulgare L.) germplasm is important for keeping diverse genetic resources available for barley improvement. 01Ab9663 (Reg. No. GP‐209; PI 677387) is a six‐rowed elite line from the cross 93Ab375//92Ab5189/M83. 93Ab375 was derived from the cross Russell/82Ab2322//'Morex', and 92Ab5189 was the result of the cross 83Ab5432/85SR40. 01Ab9663 was advanced via the bulk method from the F2 to F5 generations. 01Ab9663 exhibited a 126 and 105% yield advantage over 'Morex' and 'Tradition', respectively, within 37 locations years of testing in our irrigated trials. It showed on average 81.8% malt extract, significantly higher than all the checks from 21 trials. 01Ab9663 has a semidwarf stature with strong straw, a desirable trait for lodging resistance. These excellent character traits make 01Ab9663 a good choice for germplasm development of future malt and feed lines.